2000
DOI: 10.1007/s101269900028
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Novel Repeated Sequences of a C-type Lysozyme Gene in Japanese Flounder (Paralichthys olivaceus)

Abstract: A clone of a DNA fragment of approximately 10 kb that included a c-type lysozyme gene of Japanese flounder (Paralichthys olivaceus) was isolated from a Japanese flounder genomic DNA library. This clone was subcloned, and the nucleotide sequence of the c-type lysozyme gene was determined. The flounder c-type lysozyme gene, which consisted of 3,617 bp, was found to be composed of four exons and three introns. The transcription start site was determined to be 44 bp upstream of the ATG codon by primer extension an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
69
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 22 publications
8
69
0
Order By: Relevance
“…c-type lysozymes have been isolated from many vertebrates and insects (Prager & Jollès 1996, Qasba & Kumar 1997. In fishes, complete coding sequences of the c-type lysozymes of Japanese flounder (Hikima et al 1997) (GenBank #AB050469), turbot (GenBank #AJ250732), rainbow trout (Dautigny et al 1991) (GenBank #X59491), zebra fish (GenBank #AF402599) and common carp (GenBank #AB027305) have been reported. G-type lysozymes have also been characterized in geese, chickens, black swans and ostriches (Canfield & McMurry 1967, Simpson et al 1980, Schoentgen et al 1982, Nakano & Graf 1991, and gtype lysozyme full-length cDNA sequences have been reported from chickens (Nakano & Graf 1991), flounder (Hikima et al 2001), carp (GenBank #AB084624), mice (GenBank #AK009014) and humans (GenBank #BC029126).…”
Section: Introductionmentioning
confidence: 99%
“…c-type lysozymes have been isolated from many vertebrates and insects (Prager & Jollès 1996, Qasba & Kumar 1997. In fishes, complete coding sequences of the c-type lysozymes of Japanese flounder (Hikima et al 1997) (GenBank #AB050469), turbot (GenBank #AJ250732), rainbow trout (Dautigny et al 1991) (GenBank #X59491), zebra fish (GenBank #AF402599) and common carp (GenBank #AB027305) have been reported. G-type lysozymes have also been characterized in geese, chickens, black swans and ostriches (Canfield & McMurry 1967, Simpson et al 1980, Schoentgen et al 1982, Nakano & Graf 1991, and gtype lysozyme full-length cDNA sequences have been reported from chickens (Nakano & Graf 1991), flounder (Hikima et al 2001), carp (GenBank #AB084624), mice (GenBank #AK009014) and humans (GenBank #BC029126).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was reported that the number of the genes significantly increases after experiment testing bacterial attacks. For Paralichthys olivaceus, the gene was identified most abundantly in head kidney, spleen, and ovary [1].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it was reported that the number of the genes significantly increases after experiment testing bacterial attacks. For Paralichthys olivaceus, the gene was identified most abundantly in head kidney, spleen, and ovary [1].Oplegnathus fasciatus belongs to class of Chordata, Actinopterygii, and perciformes, and is temperate zone fish usually inhabiting in rock zones of coasts. They are distributed in all coastal areas of Korea, the Japanese coastal areas, and the Chinese coastal areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An important innate immune component is the mucus layer on the surface of fish which serves as the first line of defense against invasion between fish and its aquatic environment [37]. It is well established that skin secretions of fish contain a number of innate humoral defence factors, including complement factors [47], lectins [3], proteases [20] and lysozymes [21,38]. It is revealed that the surface mucosa of some fish also contains a range of AMPs, such as those with the molecular weight (MW)\10 kDa from Misgurnus anguillicaudatus [10,32], Pardachirus marmoratus and Pardachirus pavoninus [24,42], Pleuronectes americanus [8], Salmo salar [29], Oncorhynchus mykiss [16,17], Morone chrysops and Morone saxatilis [28], Hippoglossus hippoglossus L. [5], Parasilurus asotus [33] and Myxine glutinosa [41].…”
mentioning
confidence: 99%